ChemInform Abstract: Synthesis of Optically Active Thromboxane A2 and Leukotriene D4 Receptor Antagonists. Issue 25 (24th June 2014) - Kawazoe, Souichirou; Okamoto, Yoshinori; Yokota, Masaki; Kubota, Hirokazu; Naito, Ryo; Takeuchi, Makoto; Ieda, Shigeru; Okada, Minoru; Oriyama, Takeshi
Abstract Both the (+)‐ and (‐)‐enantiomers of title compound (I) are synthesized.